1993
DOI: 10.1080/00150199308008263
|View full text |Cite
|
Sign up to set email alerts
|

Polarized light studies of the ferroelastic domains of K3Fe5F15

Abstract: The orthorhombic ferroelastic domai ns of K 3 Fe 5 F 15 , with prototypic tetragonal tungsten bronze(TIB) structure and mixed valency 3Fe2+f2Fe3+, have been studied at R.T. in polarized light on single crystals grown by high temperature solution growth with subsequent quenching from 973K. The birefringent ferroelastic domains exhibit a remarkable linear dichroism. The principal refractive indices and the principal extinction coefficients have been measured along the crystallographic axes, identified by means o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…According to the optical studies of the orthorhombic ferroelastic domains at 298 K, 6 summarized in Figure 1, the orthorhombic domain patterns of the platelet served for optical studies are shown in Figures 2 (a)-(c) and are schematically represented in Figure 2 (d) .…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the optical studies of the orthorhombic ferroelastic domains at 298 K, 6 summarized in Figure 1, the orthorhombic domain patterns of the platelet served for optical studies are shown in Figures 2 (a)-(c) and are schematically represented in Figure 2 (d) .…”
Section: Sample Preparationmentioning
confidence: 99%
“…4 We have synthesized stoichiometric single crystals of KFEF by high temperature solution growth with subsequent quenching from 973 K, according to the condition which was deduced from thermal analysis an_ d X-ray diffraction measurements. 5 After having established in a previous work the correlation between the refractive indices, extinction coefficients and the crystallographic axes at room temperature, 6 we have undertaken in the present work optical and magnetic measurements on single crystals of KFEF at l.ow temperatures with a view to clarifying the phase sequence of KFEF and exploring potential magnetoelectric properties.…”
Section: Introductionmentioning
confidence: 99%